Proteomics study on meat quality of Malaysian broilers in comparison with indigenous chicken - Abu Hassan, Muhamad Shafiq; Nik Ahmad Kamil, Nik Nornadhirah; Hamdan, Nurul Ashima; Abd Hamid, Shafida; Muhamad Bunnori, Noraslinda (2015)
In this study, we compare the quality differences between commercial broilers and indigenous chicken muscle by using proteomics approach. Six differentially expressed between both samples were successfully identified in 2D-PAGE. Two of the proteins are enzymes involved in glycolysis (alpha-enolase and pyruvate kinase), two proteins are involved in stress regulation (heat shock 70 kDa protein and stress induced phosphoprotein) and another two proteins involved in structural proteins (myosin regulatory light chain and myozenin). In general, we suggest that broilers have a rapid metabolic rate and rapid glucose metabolism compared to indigenous chicken. We also speculate that broilers experienced various stress from internal and external compared to indigenous. In term of meat quality, broilers chicken have a lack of structural proteins composition compared to indigenous which eventually makes us suggest that broilers meat is more tender compared to indigenous chicken due to this absence.